(untitled) (Semiárida, 2020)
The present study of the genus Prosopis L. emend. BUrXart(Leguminosas Juss.), In the Province of La Pampa, Argentine, Is based on the extemal morphology. As a result 7 species, 6 varletles and 1 form are recognized, of which 2 species, 2 varieties and 1 form are cited for tlrst time for this province. A key for the Identification of the entitles, synonymy, common names, Ranquel Indian names, a description, the general distribution and their diffusion In La Pampa and a discussion of the characteristics and qualities; are given. A Iist of the studied herbarium specimens la included.